KEPATUHAN APARATUR DESA DALAM PENATAUSAHAAN PENGELOLAAN KEUANGAN DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 DI WILAYAH KECAMATAN SAMBAS KABUPATEN SAMBAS - Yuliansyah Yuliansyah; Munandar Munandar (Politeknik Negeri Batam, 2017)
The research title is the obidience of village administration office toward village financial management based on Domestic Ministry Decree No 113/2014. The objectives this research is to find out the obedience of village administration office, especially in Sambas district area, towardthe system of village finance management as regulated by Domestic Ministy No 113/2014.This research applied descriptise method with qualitative design. This research found that most of village administration offices of Sambas distric areas had followed and implemented the regulation of local goverment office No 13/2015 regarding the guideline of managing village financial system as decreed on Domestic Ministry Decree No 113/2014. The study aslo found that the village administration had narrow understanding on the some parts the financial system due to lack of technical quidence on village financial system and lack of adequate human resources of the office. As a result, some village administration did not make their financial report accordence with the regulation stated and the ministy of rural.